REPRESENTATION DU COUPLAGE HYDRO-CHIMIQUE ET MECANIQUE DANS LES ARGILES ACTIVES - LAREDJ Nadia (My University, 2010)
Different models for the description of swelling pressure in clays have been proposed in recent years. Some models are based on geotechnical properties, these models are empirical, obtained from a statistical approach, others originated from concepts of thermodynamics and an other class of models resulted from the diffusive double layer theory of Gouy and Chapman. The swelling characteristics are strongly influenced by the pore fluid chemistry and the mineralogical composition of clays. The composition of interlayer cations controls the interlayer water content. Hence, the saturated water content and the swelling pressure. This study presents the effect of osmotic potential due to chemical solute concentration changes via the use of the net stress, suction and chemical solute concentration elastic constitutive relationship. This model will represent the deformation behaviour exhibited by expansive clays. In particular, it was suggested that the determination of the stiffness of the soil with respect to chemical solute concentration could be achieved via a theoretical approach or by an empirical relationship. A set of exercises was performed to show the ability of the model to represent the trend of behaviour observed.
Keywords: swelling clay, osmotic potential, numerical model, finite element method, double layer theory.